DUODENOGASTRIC REFLUX AND HISTOPATHOLOGICAL CHANGES IN GASTRIC AND DUODENAL MUCOSA IN PATIENTS WHO UNDERWENT CHOLECYSTECTOMY - Nafi YAZICIOĞLU; Uğur GÖNENÇ; Ali Önder KARAOĞLU; Belkıs ÜNSAL; Himmet KARACA; Sadun KOŞAY (Turkish Journal of Gastroenterology, 2020)
-